ACCOUNTABILITY OF NOTARY/LAND DEED OFFICIAL FOR TRANSACTION OF LAND SALE AND PURCHASE BASED ON FAKE EVIDENCE - I Wayan Richa Arthawan; Stanislaus Atalim; Amad Sudiro (NOTARIIL Jurnal Kenotariatan, 2024)
Notary/PPAT accountability is a form of responsibility carried out by a Notary/PPAT legally for a certain action against his position, duties and authority in making an authentic deed. In a land sale and purchase transaction, when pouring all forms of data provided by the parties, if there is a sale and purchase of land based on fake document evidence to transfer ownership rights to other people's land which is not actually being traded. In this case the Notary/PPAT is not properly positioned as a party to this case, because the Notary/PPAT where all products issued by a Notary/PPAT are based on Law Number 30 of Year 2004. Meanwhile, the legal consequences of land sale and purchase agreements based on forged documentary evidence are that a deed only has the power of proof as a private deed. This study uses a normative legal method, using a case approach, statutory approach, and legal conceptual approach with primary, secondary and tertiary legal materials. The conclusion of this study is that a Notary/PPAT cannot be said to have committed a violation of the making of the Sale and Purchase Deed, because what is stated in a Notary deed is the will of the parties, and as a legal consequence of the land sale and purchase agreement based on forged documentary evidence, namely the deed becomes legally flawed because it is based on manipulative documents.